Fundamentals Of Communication Systems - G. Proakis,John; Salehi, Masoud (Boston Pearson Education Limited, 2014)
Although the book is mainly written as an undergraduate-level textbook,it can be equally useful to the practicing engineer,or as a self-study tool.The emphasis of this book is on digital communication systems,which are treated in detail in chapters 7 through 15. These systems are the backbone of modern communication systems,including new generations of wireless communication systems,satellite communiction,and data transmission networks. Traditional analog communication systems are also covered in detail in chapters 3,4 and 6.In addition,the book provides detailed coverage of the backfround required for the course in two chapters, one on linear system analysis with emphasis on the frequency-domain approach and Fourier techniques,and on probability,,random variables,and random processes
Includes: References p.897-905 , index p. 905-923
3
Keywords: Data Transmission System; Electric waves; Information Storage device; Signals and signaling